Optimal nanofluid selection for photovoltaic/thermal (PV/T) systems in adverse climatic conditions - Miqdam T. Chaichan; Hussein A. Kazem; Maytham T. Mahdi; Ali H.A. Al-Waeli; Anees A. Khadom; K. Sopian (Case Studies in Thermal Engineering)
For PV/T systems, nanofluids are used to collect thermal energy and cool the PV panels in order to generate more electricity. To date, researchers have not agreed on a name for the optimal nanofluid for photovoltaic thermal (PV/T) applications, despite extensive experiments on a variety of nanofluids and in various types of heat exchangers. In this practical study, an attempt is made to find a method for selecting the best nanofluid from a large number of these fluids. The various nanoparticles were chosen based on their availability in local markets and subjected to numerous studies including nanofluids. SWCNT, MWCNT, SiC, ZnO, TiO2, CuO, and Al2O3 particles were mixed with water (primary liquid) to form seven coolants. By examining the thermophysical properties of the prepared suspensions (SWCNT, MWCNT, SiC, TiO2, ZnO, CuO, and Al2O3), it was found that their densities increased by 0.5 %, 0.8 %, 13.3 %, 1.67 %, 11.03 %, 9.32 %, and 7.32 % compared to water, respectively. Also, the viscosity was increased by 1.83 %, 0.84 %, 11.82 %, 1.14 %, 1.43 %, 1.44 % and 3.92 % compared to water, respectively. As well as their thermal conductivities increased by 103.3 %, 81.6 %, 66.1 %, 36.6 %, 40 %, 21 %, and 27 % compared to water, respectively.Two main parts of the study were examined. Initially, tests were carried out in the laboratory at a temperature of 25 °C and a radiation intensity of 1000 W/m2. The second part of the tests was conducted outdoors under harsh climatic conditions, which are among the worst in the world, including some of the harshest weather conditions in Baghdad in July 2022. This practical study aims to use highly efficient nanofluids as heat transfer materials in photovoltaic/thermal systems. SWCNT, MWCNT, SiC, ZnO, TiO2, CuO, Al2O3, and MWCNT are used to enhance the performance of PV/T system at different testing conditions. There is a noticeable increase in electricity produced, starting at 32.39 % and ending at 118.32 %. The fluids tested at a flow rate of 9 l/min also showed interesting results. Comparing SWCNT, MWCNT, SiC, ZnO, TiO2, CuO, and Al2O3 to water cooling, the thermal efficiency was increased by 177 %, 73.14 %, 60.95 %, 32.39 %, 27.9 %, 61.91 %, and 65 %, respectively. SWCNTs achieve the lowest irreversibility values when compared to other nanofluids.